Kajian Atas Pemikiran Albert Schweitzer Tentang Kesejarahan Yesus Dan Implikasinya dalam Pendidikan Agama Kristen - Roedy Silitonga (STT Pelita Dunia, 2022)
Abstract: Albert Schweitzer's thoughts were formed from his childhood from home to university, related to his search for the historicity of Jesus in the Bible, theology, and philosophy. This search was formulated with Schweitzer’s fundamental thought that Jesus is a moral teacher, on an equal footing with other moral teachers. This is not entirely true, even though the descriptions of his books refer to the four Gospels and the Pauline epistles. He concentrated only on the humanity of Jesus and did not write an introduction to the divinity of Jesus. The thought that Jesus is a Moral Teacher became the basis of strength for Schweitzer to carry out missionary services in Lambarene, Africa, among people who were suffering and had not received formal education. This paper uses qualitative methods and literature studies with descriptive studies and theological reflection. It is hoped that this writing will be useful for every Christian to know Jesus in His status as the Son of God and man while at the same time encouraging a Bible-based and Christ-centered Christian Religious Education learning process and the formation of godly character to serve fellow human beings. Abstrak: Pemikiran Albert Schweitzer terbentuk sejak kecil dari rumahnya sampai ke perguruan tinggi, berkaitan pencariannya tentang kesejarahan Yesus secara biblika, teologi, dan filosofi. Pencarian itu melahirkan pemikiran mendasar bagi Schweitzer bahwa Yesus adalah Guru Moral, disejajarkan dengan guru moral lainnya. Hal itu tidak sepenuhnya benar, sekalipun uraian dari buku-bukunya merujuk pada empat kitab Injil dan Surat-Surat Paulus. Ia hanya memperhatikan kemanusiaan Yesus dan belum menuliskan pengenalannya akan keilahian Yesus. Pemikiran Yesus adalah Guru Moral menjadi dasar kekuatan bagi Schweitzer melakukan pelayanan misi di Lambarene, Afrika di antara orang-orang yang menderita dan yang belum mendapatkan pendidikan formal. Tulisan ini menggunakan metode kualitatif dan studi Pustaka dengan kajian deskriptif dan refleksi teologis. Tulisan ini diharapkan bermanfaat bagi setiap orang Kristen untuk mengenal Yesus dalam keadaan-Nya sebagai Anak Allah dan manusia, sekaligus mendorong adanya proses pembelajaran Pendidikan Agama Kristen yang berbasiskan Alkitab, berpusatkan Kristus, dan pembentukan karakter yang saleh untuk melayani sesama manusia.